2017
DOI: 10.1101/183137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hsf1 and Hsp70 constitute a two-component feedback loop that regulates the yeast heat shock response

Abstract: 20Models for regulation of the eukaryotic heat shock response typically invoke a negative 21 feedback loop consisting of the transcriptional activator Hsf1 and a molecular chaperone 22

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 39 publications
(29 reference statements)
4
46
0
Order By: Relevance
“…Our initial results are consistent with the longstanding view that misfolding of newly 405 synthesized polypeptides can serve as Hsf1 inducers (Baler, 1992;Masser et al, 2019), 406 presumably through recruitment of Hsp70 away from its repressive association with Hsf1 407 Krakowiak et al, 2018;Li et al, 2017). However, we have discovered an 408 alternative pathway for Hsf1 activation under conditions when newly synthesized proteins are 409 in short supply-when translational activity is low, such as following starvation or 410 pharmacological inhibition.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Our initial results are consistent with the longstanding view that misfolding of newly 405 synthesized polypeptides can serve as Hsf1 inducers (Baler, 1992;Masser et al, 2019), 406 presumably through recruitment of Hsp70 away from its repressive association with Hsf1 407 Krakowiak et al, 2018;Li et al, 2017). However, we have discovered an 408 alternative pathway for Hsf1 activation under conditions when newly synthesized proteins are 409 in short supply-when translational activity is low, such as following starvation or 410 pharmacological inhibition.…”
supporting
confidence: 80%
“…On the flip side, Hsf1 can be robustly activated 438 without a drop in pH, so long as cells are translationally active, indicating that acidification is 439 not necessary for Hsf1 activation. Recent key studies have demonstrated that production of 440 Hsp70 binding substrates that titrate Hsp70 away from Hsf1 suffices to induce Hsf1 in the 441 absence of heat shock Krakowiak et al, 2018). All these results are 442 consistent with the standard misfolding model: newly synthesized polypeptides misfold in 443 response to heat shock, leading to recruitment of Hsp70, which causes Hsf1 activation.…”
mentioning
confidence: 67%
“…Previous models of the heat shock response at the cellular level aimed to characterize the importance and functionality of different aspects of the control circuit, including transcriptional, post-transcriptional and post-translational regulation, as well as the feedforward and feedback loops (Guisbert et al, 2008;Castells-Roca et al, 2011;Rieger et al, 2005;Petre et al, 2011;El-Samad et al, 2005;Abravaya et al, 1991;Krakowiak et al, 2017;Kurata et al, 2006). These models vary significantly in the level of detail at which different processes are modeled.…”
Section: Discussionmentioning
confidence: 99%
“…These models vary significantly in the level of detail at which different processes are modeled. In bacteria and yeast, the resolution of available experimental data allowed for assignment of functional roles to different branches of the regulatory circuits (El-Samad et al, 2005;Kurata et al, 2006) and the association of HSP-70 with HSF-1 (Krakowiak et al, 2017), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multiple studies have pointed to Hsp70 as the primary and direct negative regulator of Hsf1 activity (15,16,22). Since Hsp70 is a major transcriptional target of Hsf1, these two proteins form a negative feedback loop that controls the dynamics of HSR induction (23). Although Hsp70 has emerged as a key repressor of Hsf1, roles for the other chaperones have not been ruled out.…”
Section: Introductionmentioning
confidence: 99%